Alternative model and approach for determining microbial heterotrophic activities in aquatic systems. - Dietz, A S (1977)
Increasing amounts of high-specific-activity tritiated organic compounds were added to samples of several natural waters such that in situ substrate concentrations might be approximated. The uptake responses by the native heterotrophic microflora suggested that (i) heterotrophic populations metabolize the added nutrients, but (ii) these responses are not necessarily a reflection of Michaelis-Menten enzyme kinetics. The uptake kinetics appeared to be due to dilution of the naturally occurring metabolite by added radioactive substrate and physiological responses of the microflora to organic enrichment.